Dolomitos lacustres da Formação Alcântara (Cretáceo Superior), Bacia de São Luís, Maranhão: paleoambiente, microbialitos e icnofósseis - SOARES, Tatianny Cristina Queiroz (2022)
The Alcântara Formation, dated between the Neoalbian and Cenomanian (~105 Ma), presents whitish dolomitic layers with microbialitic structures in lacustrine deposits located at Baronesa beach. The objective of this research is to understand the genesis of these dolomites based on the interpretation of their sedimentary and biogenic structures, and to make paleoenvironmental and paleoecological considerations. For this, field work was carried out, and after this phase, there was work in the laboratory with sample treatment, petrographic, microbial structures and ichnological analysis. Four carbonate microfacies were described in the studied deposits, namely: massive dolomudstone (MF1); dolomudstone with irregular and crenulated laminations (MF2); dolomudstone with wavy/wrinkled laminations (MF3) and dolomicrosparite with irregular lamination (MF4). The microfacies are very similar to each other, and have common constituents such as microcrystalline dolomite, peloids, terrigenous grains and rare bioclasts, the main difference between them being the texture. Despite interpreting these features as microbialites, we prefer not to use the proper nomenclature for bioconstructed deposits proposed by Dunham (1962) until their biogenicity is confirmed. Thus, the nomenclature for abiogenic rocks was used, but whenever possible highlighting the microbial features. Five trace fossils were also described, namely Palaeophycus, Phycodes, Taenidium, Thalassinoides and Rhizocorallium. Finally, it was possible to propose a new evolutionary model for the area studied in six stages: 1) Subsidence and deposition of clay and silt layers in probably saline to brackish waters; 2) Increased salinity with precipitation of carbonates through the action of microorganisms and suppression of siliciclastic sedimentation; 3) Followed by intense and temporary bioturbation by deposit-feeders organisms; 4) Permanent colonization of the substrate by decapod crustaceans that built galleries in the cohesive carbonate and the installation of vegetation; 5) The level of the lake starts to decrease, probably related to a greater aridity and high rate of evaporation, exposing the dolomites to the action of meteoric waters and, finally, 6) there is an increase in the water level inside the lagoon and consequently the increase in fine siliciclastic sedimentation rate that suppressed carbonate sedimentation. This cycle was repeated at least three more times until the beginning of the transgressive phase that gave rise to the siliciclastic deposits of the Cujupe Formation.